The Implementation of Law Number 21 of 2008 Concerning Sharia Banking on Sharia Financial Institutions is Underway Sharia Economic Law Perspective - Rahma, Fuji Alia; Noviarita, Heni; Zaharah, Rita (Universitas Islam Negeri Raden Intan Lampung, 2024)
The role of Law Number 21 of 2008 concerning Sharia Banking for Islamic financial institutions is very large, because currently Islamic financial institutions (LKS) have legal certainty to be able to carry out Islamic economic activities in Indonesia. The existence of the Sharia Banking Law provides an answer to the sustainability of the Islamic economy in Indonesia as a whole, both those that include the activities of Islamic financial institutions in the form of banks and non-banks. In this context, what is studied is the basis of sharia economic law and the implementation of Law Number 21 of 2008 in society. The purpose of this research is also to find out the legal position of sharia economics in Indonesia in accordance with the law being studied. This study uses library research with a qualitative research method, also known as a qualitative method of literature study. The results of this study are in accordance with the rules stated in its implementation, strengthened by a normative juridical point of view, which is the legal umbrella in the settlement of sharia economic disputes in Indonesia, namely Law Number 3 of 2006 concerning Religious Courts and Law Number 4 of 2004 about the Judicial Power as a form of upholding legal justice for the community in carrying out sharia economist activities in Indonesia, which is a reflection for the State of Indonesia in providing social justice for all Indonesian people. Keywords: Financial Institutions; Banking; Sharia;